Work-Life Balance as a Best Practice Model of Human Resource Management: A Win-Win Situational Tool for the Employees and Organizations - Tariq, Amber; Aslam, Hassan Danial; Siddique, Anam; Tanveer, Asif (Richtmann Publishing, 2012)
Organizations focus upon increased revenue generated by its employees, competitive workforce and employeededication for achieving its strategic goals in order to meet the challenges of 21st century. However, in this era of hypercompetition work life balance of employees’ at all managerial levels has been affected enormously. This exploratory studydeliberates upon a brief elaboration of work-life balance, its importance for the organizations and the various emergingpractices/initiatives associated with it. The current research builds upon the considerable knowledge related to the theory andpractices of Work-life balance from extensive Meta-analysis of literature. The findings reveal that work-life balance is bothimportant for the organization and for its employees particularly in current dynamic organizational scenarios. It helps theorganization to improve productivity, efficiency, competitiveness, morale and hence gain a competitive edge. Similarlyemployees are benefited from work-life balance initiatives through increased motivation to work, enhanced satisfaction,empowerment and ultimately more commitment to the organization.